??????? ????????? ???? ?? ? ??? ????? 1820 - 1801 - ??? ?????? ???? ????? (مجلة كلية التربية, 2020)
The united states of America had a clear presence in North Africa this interest increased after it gained independence in 1776 in order to gain privileges in this region Tripoli had the west’s share of America interest , which was viewed by yusuf al Qarmanli as his opinion , and he was about to enter the arena of conflicts and agreements then led to their ealm in 1820.